Techniques and Technologies for Web-Based Applications Development: Exploring the evolution of web-based applications (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The belief of the service of web, as well as the interpretations of the similar fundamental principles, have certainly not been sufficiently upgraded. The thought responsible for the common condition "web application," as well as its meaning performs certainly not cover the assorted forms of applications offered in these times, which take advantage of the service of the web. This paper gives an outline of the generic web applications. It then prolongs the conversation via a contemporary point of view, planning the sunshade term "web-based function" to address a more excellent range of devices, which are not probably to become dealt with by the condition "web application". This paper provides the techniques and technologies related to the development of web-based applications.